Service life evaluation of RC T-girder under carbonation considering cold joint and loading effects. (30th November 2019) - Koh, Tae-Ho; Kim, Moon-Kyum; Yang, Keun-Hyeok; Yoon, Yong-Sik; Kwon, Seung-Jun
Highlights: Quantitative evaluation of cold joint effect on carbonation. Combined effect of cold joint and induced stress on carbonation velocity. Evaluation of varying service life of T-Girder considering stress level and cold joint. Greatly reduced service life in tensile zone with cold joint regardless of crack initiation. Effective maintenance plan through cold joint and loading level. Abstract: Carbon dioxide concentration is steadily increasing in large cities. Consequently, durability evaluation of RC (Reinforced Concrete) structures considering carbonation is becoming a serious issue. Construction joints are used for the effective construction of concrete structures. However, cold joints which are caused by delayed placing and poor surface treatment are vulnerable to shear force and the inflow of carbon dioxide. In this study, an accelerated carbonation test was performed for normal-strength concrete using NPC (Normal Portland Cement) and slag after applying tensile and compressive stresses. The carbonation characteristics were quantified considering the effects of cold joint and the induced stress, and structural analysis was performed using the section laminae approach for a 2-span continuous reinforced concrete T-beam bridge. The service life of top and bottom concretes was evaluated considering the calculated stress, existing carbonation velocity equation, and carbonation function according to the stress. The service life showed a similar trend to that of the applied moment. Changes of 103.6%–64.7% (NPC) and 78.0%–108.8% (slag) were observed on the top surface, whereas changes of 103.8%–65.9% (NPC) and 112.9%–79.6% (slag) were observed on the bottom surface. The service life significantly decreased owing to the increasing carbonation depth for the cold joint in the tension part. This suggests that special care should be taken for cold joints during maintenance.